Improving Personal Hygiene of Scabies Sufferers in Adolescents Using the Peer Group Method - Prameswari, Veryudha Eka; Sa'diyah, Lida Khalimatus (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Cleanliness of the skin and mucous membranes is very important because the skin is the body's first line of defense from germs. Low levels of hygiene and sanitation as well as socio-economic conditions are factors that trigger the occurrence of scabies. Scabies or scabies is an infectious skin disease caused by the infestation of the mite Sarcoptes scabies and is zoonotic. Scabies is one of the most common dermatological conditions, accounting for the majority of skin diseases in developing countries. Globally, it affects more than 130 million people at any time Objectives: This research aims to improve Personal Hygiene for scabies sufferers in adolescents using the Peer Group method Methods: The method in this study was to use the peer group method with a research design using a pre-experiment with the type of one-group pretest-posttest design. The population is all female students at the Roudlotun Nasyiin Islamic Boarding School, namely 24 students, the sampling uses total sampling with a sample of 24 respondents. The study was conducted for 3 weeks Results: The results of this study are that all respondents before being given the peer-group method were included in the inappropriate personal hygiene category as many as 24 respondents (100%) and after being carried out with the peer group method almost all of the respondents were included in the personal hygiene category right 22 respondents (91.7 %), and 2 respondents (8.3%) still did not do personal hygiene correctly Conclusions: This study concludes that there is an influence of the peer group education method on the personal hygiene of female students at the Roudlotun Nasyiin Islamic Boarding School. The peer group method makes it easier to provide information about personal hygiene in dealing with scabies sufferers, namely through peers, those who live together will know each other so they can remind each other about the personal hygiene of female students.